2013
DOI: 10.1038/nprot.2013.115
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative bisulfite sequencing of 5-methylcytosine and 5-hydroxymethylcytosine

Abstract: To uncover the function of and interplay between the mammalian cytosine modifications 5-methylcytosine (5mC) and 5-hydroxymethylcytosine (5hmC), new techniques and advances in current technology are needed. To this end, we have developed oxidative bisulfite sequencing (oxBs-seq), which can quantitatively locate 5mC and 5hmC marks at single-base resolution in genomic DNA. In bisulfite sequencing (BS-seq), both 5mC and 5hmC are read as cytosines and thus cannot be discriminated; however, in oxBS-seq, specific ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
203
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 310 publications
(217 citation statements)
references
References 28 publications
1
203
0
Order By: Relevance
“…We note that the bisulphite data do not rule out the presence of hm 5 C, which is also resistant to bisulphite conversion. Oxidative bisulphite sequencing, which can distinguish m 5 C and hm 5 C in DNA (Booth et al , 2013), resulted in degradation of the RNA. However, hm 5 C was not observed upon ABH1 oxidation in vitro and had no beneficial effect in ribosome binding assays, suggesting that this modification might not play a major role for mt‐tRNA Met .…”
Section: Resultsmentioning
confidence: 99%
“…We note that the bisulphite data do not rule out the presence of hm 5 C, which is also resistant to bisulphite conversion. Oxidative bisulphite sequencing, which can distinguish m 5 C and hm 5 C in DNA (Booth et al , 2013), resulted in degradation of the RNA. However, hm 5 C was not observed upon ABH1 oxidation in vitro and had no beneficial effect in ribosome binding assays, suggesting that this modification might not play a major role for mt‐tRNA Met .…”
Section: Resultsmentioning
confidence: 99%
“…However, the recent discovery of endogeneous TET-mediated conversion of 5-methylcytosine (5mC) back to the unmethylated state through 5hmC, 5fC, and 5caC intermediates has raised some concerns over the interpretation of the past methylation data produced by bisulfite modification technique, since this technique is unable to distinguish between 5mC and 5hmC, leaving them both as cytosines [133]. Although some new techniques such as oxidative bisulfite sequencing have been developed to make this distinction possible, the number of studies using such methods yet remains limited [134,135]. Taken together, although the exact cause and effect relationship between epigenetics and male infertility has not been elucidated, further investigation of this area holds a significant potential and great promise for understanding the molecular mechanisms of infertility.…”
Section: Resultsmentioning
confidence: 99%
“…41 To examine this possibility, we determined the 5hmC content of the hypermethylated ERV-9 LTR by oxBS-Sseq. 53 The results showed that 5hmCs comprised a very minor portion of total 5mCs (< 5%; Fig. 2e).…”
Section: Hypermethylated Erv-9 Ltr Possesses In Vivo Enhancer Activitymentioning
confidence: 96%